Republic of Moldova : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criterion; Staff Report; Staff Statement; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Second Review Under the Poverty Reduction and Growth Facility (PRGF). Program performance has been generally satisfactory. The quantitative performance criteria were observed, as was most of the structural conditionality. One structural performance criterion was missed at end-December: the increase in tariffs for district heat and water was briefly delayed in Chisinau. IMF staff supports completion of the review and granting a waiver for nonobservance of the structural performance criterion. The authorities' commitment to implement supplementary measures provides assurance that the program's objectives remain attainable.